(untitled) (Economic studies journal, 2025)
The study aims to shed light on the phenomenon of hidden economy in Libya, by measuring its size and main indicators, using annual data covering the period 2000-2021, with inductive method to estimate the size of the hidden economy by calculating the money in circulation to demand deposit ratio, analyzing both normal and abnormal money demand, as well as measuring the share of the hidden economy in both oil and non-oil GDP. The study’s main: an increase of the hidden economy’s size to a high level of 33.80% in 2019, The study also found that the share of the abnormal demand in currency circulation reached 53.11% in 2019, while its share of non-oil GDP reached its highest value in 2021 at 35.6%, as a result of the events that the country had experienced. The study was concluded with a list of recommendations, the most important being the need to create a stable economic climate, activate legislations and legal frameworks, and fight administrative and financial corruption to combat illegal activities The study conclusion recommended, the most important being the need to create a stable economic climate, activate legislations and legal frameworks, and fight administrative and financial corruption to combat illegal activities